EFFECT OF HERBAL DURGS AND MINERALS ON FERTILITY IN POST PARTUM ANESTRUS OSMANABADI GOATS - PATIL, A D; RAGHUWANSHI, D S; KUMBHAR, U B; MAINl, SHIV (The Indian Journal of Animal Reproduction, 2011)
A clinical study was carried in a flock of Osmanabadi Goats reported with the history of infertility and postpartumanestrus. A total of 20 Osmanabadi Goats were divided into two equal groups. Group-I (n=10) was untreatedcontrol and animals of treatment group II (n=10) were administered orally with herbal uterine tonic and restorative Uterine cleanser (Exapar)@20 ml/goat/day for 5 days alongwith herbal heat inducer (Cap. Janova) @2 cap/day/ goat for three days and tablet mineral supplementation (Mintrus) @ 1 Tab/day/goat for 20 days. Induction ofoestrus was 80 % in group-II within 106.87.±7.51 hrs and 75 % conceived with 1.83 services per conceptionwhereas in control group I, 30 % estrus was observed within 185.5±10.89 hrs and 33.33 % conceived with 3.00services per conception. It may be concluded that uterine cleanser is a potent herbal ecbolic and which alongwith herbal heat inducer and mineral supplementation has lead to induction of fertile post partum estrus and higher conception rate in Osmanabadi goats.
Keywords: Herbal heat inducer; Mineral supplementations; Post partum anestrus; Osmanabadi goat